Taking sides : Clashing views in world history Volume 1, The ancient world to the pre-modern era - Mitchell, Joseph R.; Mitchell, Helen Buss. (Boston : McGraw-Hill Higher Education, 2012)
This volume presents current controversial issues surrounding pertinent topics in the study of world history in a debate-style format designed to stimulate student interest and develop critical thinking skills. The topics are framed with a general summary and introduction, and a postscript or challenge questions. This work features an annotated listing of selected World Wide Web sites and an online instructor's resource guide with testing material available.
Unit 1. The ancient world. issue 1. Was an Aryan invasion responsible for the demise of the Indus Valley civilization? ; issue 2. Was Sumerian civilization exclusively male dominated? ; issue 3. Were the Spartans fighting for a compromised view of freedom at Thermopylae? ; issue 4. Does Alexander the Great deserve his historical reputation? ; issue 5. Did Christianity liberate women? ; issue 6. Were internal factors responsible for the fall of the Roman Empire? -- Unit 2. The Medieval/Renaissance worlds. issue 7. Did the Byzantine Empire benefit from the rule of Justinian and Theodora? ; issue 8. Did environmental factors cause the collapse of Maya civilization? ; issue 9. Could the Crusades be considered a Christian holy war? ; issue 10. Does the modern university have its roots in the Islamic world? ; issue 11. Did women benefit from the Renaissance? ; issue 12. Did China's worldview cause the abrupt end of its voyages of exploration? -- Unit 3. The premodern world. issue 13. Did Christopher Columbus's voyages have a positive effect on world history? ; issue 14. Was gender a major issue in Queen Elizabeth I of England's Reign? ; issue 15. Did Martin Luther's reforms improve the lives of European Christians? ; issue 16. Were the witch-hunts in premodern Europe misogynistic? ; issue 17. Was the Scientific Revolution revolutionary? ; issue 18. Did the British Enlightenment pave the way for the modern world?
Includes bibliographical references.
Keywords: World history; History, Ancient; Civilization, Ancient; Middle Ages; Civilization, Medieval